Repurchase Intention Pada Korean Skincare Product Di Surabaya - Sesilya Kempa; Erika Gotami (BIP's JURNAL BISNIS PERSPEKTIF, 2019)
This study aims to determine whether or not the influence of country of originimage and perceived value on repurchase intention with word of mouth as anintervening variable on Korean skincare products in Surabaya. The type ofresearch used is quantitative research. The population in this study were peoplein Surabaya who had used and purchased korean skincare products of the same type at least 3 (three) times and the samples used in this study were 100 people.This study uses Partial Least Square (PLS). The results showed that the country oforigin image had an effect on word of mouth and repurchase intention, perceivedvalue had an effect on word of mouth and repurchase intention, and word ofmouth had an effect on repurchase intention. Word of mouth is proven to mediatethe effect of country of origin image and perceived value on repurchase intention